Aerodynamics Improvement of NACA 0015 by Using Co-Flow Jet - James Julian; Waridho Iskandar; Fitri Wahyuni (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2022)
This study analyzes co-flow as active flow control in the object of the airfoil. NACA 0015 is the airfoil used in this study. The airfoil was then modified to add co-flow jet features. Co-flow jet was placed on the upper chamber to analyze its effect on airfoil performance. Further, the Co-flow jet was studied by varying the injected mass flow rate () in the injection slot. The variation of is 0.15, 0.20, and 0.25 kg/s. The study used CFD with the governing equation RANS. Reynolds Averaged Navier Stokes combined with turbulence model to solve all equations. Two equations for the turbulence model are used in this study. Specifically, this study discusses the aerodynamics of the airfoil, i.e., lift force, drag force, and fluid flow visualization, such as pressure contour and velocity contour. Co-flow jets can improve the aerodynamics of airfoils. The bigger the injected, the higher the lift coefficient increases. On the other hand, the drag force will be reduced as the number of injected fluid flow increases. Because of that, the airfoil efficiency will be better if using a co-flow jet. However, the Cl/Cdcurve peak shifts to smaller as the injection fluid flow are bigger. The fluid flow visualization by velocity contour on AoA=20° revealed that the co-flow jet could overcome separation.